Coping rarely takes place in a social vacuum: Exploring antecedents and outcomes of dyadic coping in coach-athlete relationships. (May 2017) - Staff, Helen R.; Didymus, Faye F.; Backhouse, Susan H.
Abstract: Objectives: Despite widespread acceptance that coping is an interpersonal phenomenon, sport psychology research has focused largely on athletes' and coaches' ways of coping individually. The aim of this study was to qualitatively explore coping from an interpersonal perspective (i.e., dyadic coping) in coach-athlete relationships. Methodology and methods: Antecedents and outcomes of dyadic coping were discussed with five coach-athlete dyads. We conducted individual interviews with athletes and coaches and then one interview with each coach-athlete dyad. Interviews were analyzed using dyadic analysis and composite vignettes were created to present the data. Methodological rigor was enhanced by focusing on credibility, resonance, rich rigor, significant contribution, and meaningful coherence. Results: Five themes were identified. These represented the essence of dyadic coping (theme: the essence of dyadic coping), antecedents of dyadic coping (themes: lock and key fit, friendship and trust, communication of the stressor), and outcomes of dyadic coping (theme: protection and support). The first theme captures coaches' and athletes' understanding of dyadic coping. The antecedent themes represent the factors that were necessary for dyadic coping to occur. Protection and support relates to the positive nurturing environment that was discussed as an outcome of dyadic coping. Conclusion: The results extend published research by exploring antecedents and outcomes of dyadic coping in sport. The findings highlight that dyadic coping was prevalent in coach-athlete relationships when various antecedents (lock and key fit, friendship and trust, communication of the stressor) existed. Protection and support were pertinent outcomes of dyadic coping that contributed to personal and relationship growth. Highlights: Close coach-athlete relationships stimulate dynamic, interpersonal coping processes. Dyadic coping is enabled by a perceived 'lock and key' fit in sport relationships. Friendship and trust foster and nurture dyadic coping in athletes and coaches. Stress that is communicated by the coach or the athlete can influence dyadic coping. Dyadic coping provides mutual protection and support for coaches and athletes.